2016
DOI: 10.1075/lab.15010.val
|View full text |Cite
|
Sign up to set email alerts
|

Experience with code-switching modulates the use of grammatical gender during sentence processing

Abstract: Using code-switching as a tool to illustrate how language experience modulates comprehension, the visual world paradigm was employed to examine the extent to which gender-marked Spanish determiners facilitate upcoming target nouns in a group of Spanish-English bilingual code-switchers. The first experiment tested target Spanish nouns embedded in a carrier phrase (Experiment 1b) and included a control Spanish monolingual group (Experiment 1a). The second set of experiments included critical trials in which part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…Thus, the current experimental setting simulates quite accurately the situation in which children are exposed to the use of unknown (real or not) words in their natural use of Spanish. The generalized use of MASC has been also attested in many studies on mixed DPs containing a Spanish Det and the lexical insertion of an English N (Liceras et al 2008;Valdés Kroff et al 2017) or of a Basque N (see Badiola andSande 2018 but Couto et al 2016).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, the current experimental setting simulates quite accurately the situation in which children are exposed to the use of unknown (real or not) words in their natural use of Spanish. The generalized use of MASC has been also attested in many studies on mixed DPs containing a Spanish Det and the lexical insertion of an English N (Liceras et al 2008;Valdés Kroff et al 2017) or of a Basque N (see Badiola andSande 2018 but Couto et al 2016).…”
Section: Discussionmentioning
confidence: 91%
“…(a) morpho-phonological cues such as an -a ending on a N are associated with FEM, whilst an -o ending on a N is associated with MASC (Harris 1991); other endings like -n or -e have some or no clear preference for one of them (see Teschner and Russell 1984 for gender frequencies in Spanish corpora, as illustrated by the MASC/FEM alternation (1a/2a and 1b/2b)); (b) analogical gender, according to which the English word inserted in a mixed Spanish DP is assigned the gender corresponding to the Spanish equivalent word-e.g., galleta 'cookie-FEM' (1a), libro 'book-MASC'(1b); (c) (masculine or feminine) default gender, according to which an inserted English N tends to be assigned MASC gender (2a, 2b), whilst some Basque-Spanish bilinguals tend to assign FEM to an inserted Basque word ending in -a, such as ariketa and idazlana (2c, 2d) regardless of its analogical gender (ariketa = Sp 'ejercicio-MASC' and idazlana = Sp: 'redacción-FEM') (see Couto et al 2016;Cuza and Pérez-Tattam 2015;Imaz Agirre 2016;Liceras et al 2018;Liceras et al 2008;Munarriz et al 2018;Valdés Kroff et al 2017).…”
Section: Strategies For Gender Markingmentioning
confidence: 99%
“…Additionally, the critical words (codeswitch and matched control) adhered to the following criteria: all were nouns (mostly nouns in prepositional phrases or direct objects), did not contain any diacritic markers, and the masculine Spanish determiners were used before all codeswitched English nouns. Previous research has shown that Spanish-English bilinguals tend to default to using the masculine determiner 'el' in determiner-noun codeswitches from Spanish to English, even when the English noun is grammatically feminine in Spanish (e.g., el fight where the translation of fight, lucha, is grammatically feminine; Pfaff, 1979;Valdés Kroff et al, 2016). No critical words were repeated anywhere in the task.…”
Section: Participants 22mentioning
confidence: 99%
“…The surface form of codeswitched speech thus ultimately reflects the end of a long chain of complex processing events, including production-internal processes (Levelt, 1989) as well as interactions between the production and comprehension systems (e.g., Kootstra, van Hell, & Dijkstra, 2010; Loebell & Bock, 2003). On the flip side, listeners' responses to codeswitched speech can provide an index of their expectations given previous experience processing a particular linguistic input (Valdés Kroff, Dussias, Gerfen, Perrotti, & Bajo, in press). In sum, codeswitched speech presents a rich and relatively transparent opportunity for investigating the ways in which the members of a speech community come to produce and comprehend variation in linguistic form.…”
Section: Why Codeswitched Speech?mentioning
confidence: 99%